Criterios de intervención sostenible para la articulación urbana del centro histórico y la ciudad contemporánea (2020)
Cities are home to more than 50% of the planet's population and are expected to reach a higher percentage in the coming years, this figure is equivalent to the high levels of pollution, pollution and energy expenditure, aspects that go hand in hand with planning of housing areas in the construction of the urban fabric. The increase in global population leads to the distribution of goods and services, as well as the supply of vital supports of water, energy or food security, causing a negative impact on ecosystems with the excessive extension of the territory and the morphological imbalance of the transformations of the landscape. The present investigation is developed from the planning of the urban model of Buga - Valle del Cauca, taking into account the contrasts of the landscape generated from the historical center and the contemporary city, as a consequence of the territorial transformations that emerged over time. . The local ecosystem, characterized by the Guadalajara river and the central Cordillera, are natural elements of vital importance, since they are responsible for linking and oxygenating the urban fabric, conserving the municipality's fauna and flora biodiversity. The purpose of the proposal is to generate sustainable intervention criteria for the articulation of the historic center and the contemporary city, based on the conservation and enhancement of the landscape characteristics of the context; which are projected to improve social dynamics with the urban environment, prolonging the life of the heritage and the local ecosystem.